Factors Affecting Treatment Adherence Among Patients with Tuberculosis in Indonesia: Literature Review - Fahrul Islam; Haeranah Ahmad; Nurbaya; Masnaeni Ahmad; Ansar; Kadar Ramadhan; Muhammad Syukri; Syafran Arrazy; Agung Aji Perdana; Deborah Siregar; Nining Ade Ningsih; Ikes Dwi Astuti; St. Kadijah Hamid; Asrul Hamonangan Pasaribu (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: Tuberculosis (TB) is the leading cause of death from infectious diseases in the world and Indonesia is the second largest contributor to TB cases after India. Treatment adherence problems are a major obstacle to TB elimination. The purpose of this Literature Review is to determine the factors that affect treatment adherence among TB patients in Indonesia. Methods: Literature obtained from Science Direct, PubMed, and Google Scholar; published from 2018 – 2023, research from reputable international journals and from national journals at least with SINTA 3, located in Indonesia. Indonesian and English with full text of all types of research designs. Article selection was carried out using the method